Effects of Leaching Parameters on the Dissolution of Nickel, Cobalt, Manganese and Iron from Caldag Lateritic Nickel Ore in Hydrochloric Acid Solution - Top, Soner; Kursunoglu, Sait; Ichlas, Zela Tanlega (Taylor & Francis Ltd, 2020)
The effects of leaching parameters on the metal dissolutions from Caldag laterite ore using hydrochloric acid at atmospheric pressure were investigated. The following leaching parameters were examined to understand their effects on the dissolution of the metals: hydrochloric acid concentration, solid/liquid ratio, particle size, leaching temperature and time. Extractions of 95.8%Ni, 94.5%Co and 94.3%Mn into the leach solution were obtained along with a substantial amount of iron (81.5%) under the following conditions: 3.0 M HCl concentration, 90 degrees C leaching temperature, 8 h leaching time, 1/5 solid/liquid ratio and -0.053 mm particle size. The hydrochloric acid consumption under these optimum conditions was found to be 543 kg t(-1)ore. The results indicated that hydrochloric acid concentration and leaching temperature were the most important parameters affecting metal dissolutions. It was found that the dissolution of nickel did not exhibit a good linear correlation to that of manganese, which suggested that considerable amounts of nickel were not hosted in asbolane phase but also in other mineral phases such as goethite, haematite and clays. It was, however, found that most of the cobalt appeared to be hosted in asbolane. The semi-quantitative mineral analyses revealed that mineral dissolution order was as follows: calcite > goethite > haematite > lizardite >= chlorite-serpentine > asbolane > albite > kaolinite.
Top, Soner/0000-0003-3486-4184; Kursunoglu, Sait/0000-0002-1680-5482; Ichlas, Zela/0000-0003-2550-5948
Keywords: Laterite; Caldag; Hydrochloric Acid; Nickel Dissolution; Cobalt Dissolution